Evaluation of quality of life after septorhinoplasty using Rhinoplasty Outcome Evaluation questionnaire - Aditiya Saraf; Nitika Gupta; Monica Manhas; Parmod Kalsotra (The Egyptian Journal of Otolaryngology, 2023)
Abstract Background To assess satisfaction level of patients undergoing septorhinoplasty pre- and post-operatively using Rhinoplasty Outcome Evaluation (ROE) questionnaire. Methods The present prospective study, after approval by Institutional Ethics Committee, was conducted in the Department of ENT, SMGS Hospital, from March 2021 to November 2022 on 83 patients who underwent septorhinoplasty. Demographic and clinical characteristics (age, gender, education, technique of surgery) of all participants were recorded. All patients were asked to answer the Rhinoplasty Outcome Evaluation (ROE) questionnaire 1 day prior to surgery. Postoperative ROE questionnaire was asked at the 6th month in ENT OPD by the same researcher. Results In our study, the mean preoperative total ROE score was 32.17 ± 5.38, and the mean postoperative total ROE score was 87.11 ± 5.39, the difference being statistically significant (p = 0.0039). Higher post-operative satisfaction score (89.7 ± 5.64) was seen in patients aged more than 35 years, as compared to younger patients (78.4 ± 5.8). In our study, upon gender-wise comparison, there was more statistically significant satisfaction in male patients than female patients postoperatively (p = 0.0022). Better postoperative ROE score was seen in lower literacy group (88.9 ± 6.73) than higher literacy group (83.3 ± 5.63). However, both open and closed techniques showed statistically insignificant difference in postoperative ROE score (p = 0.388). Conclusion Based on the Rhinoplasty Outcome Evaluation (ROE) questionnaire, our study showed that septorhinoplasty significantly improved quality of life in majority of our study subjects in terms of both aesthetic as well as functional parameters.